FREQUENCY OF HYPERNATREMIC DEHYDRATION IN CHILDREN WITH SOME AND SEVERE DEHYDRATION (The Research of Medical Science Review, 2024)
Background: Diarrhea and dehydration in children are often accompanied by electrolyte abnormalities, including hypernatremia, which can worsen clinical outcomes. Objective: To determine the frequency of hypernatremic dehydration in children with varying degrees of dehydration. Methods: A cross-sectional study was conducted at the Department of Pediatrics, PAEC General Hospital, Islamabad, enrolling children aged 6 to 60 months with diarrhea and dehydration through non-probability consecutive sampling. After ethical approval and informed parental consent, demographic data were collected. Venous blood samples were drawn under aseptic conditions to assess serum sodium levels, and hypernatremia was recorded. Data were analyzed using SPSS version 22. Results: A total of 201 children were included (mean age: 29.64±14.5 months), with 56.2% male and 43.8% female patients. Diarrhea duration averaged 4.84±2.1 days. Some dehydration was observed in 69.7% of cases, while 30.3% exhibited severe dehydration. Rotavirus vaccination was reported in 80.6% of participants. Mean serum sodium level was 142.67±6.9 mEq/L, and hypernatremia was present in 16.4% of patients. Hypernatremia was significantly more common in cases of severe dehydration (34.4%) than in cases of some dehydration (8.6%), with a p-value of 0.001. Conclusion: Hypernatremia is prevalent among children with diarrhea and dehydration, especially in those with severe dehydration, highlighting the need for prompt electrolyte management in these patients.